2022
DOI: 10.3390/antiox11081513
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of 1,2-Dicarbonyl Compounds in Postprandial Responses Mediated by Food Bioactive Components and Mediterranean Diet

Abstract: Glycoxidative stress with the consequent generation of advanced glycation end products has been implied in the etiology of numerous non-communicable chronic diseases. During the postprandial state, the levels of 1,2-dicarbonyl compounds can increase, depending on numerous factors, including characteristics of the subjects mainly related to glucose metabolism disorders and nutritional status, as well as properties related to the chemical composition of meals, including macronutrient composition and the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 199 publications
0
3
0
Order By: Relevance
“…Polyphenols and foods rich in polyphenols were found to inhibit food lipid peroxidation in stomach medium co-oxidation of vitamins and cholesterol and production of primary and secondary ALEs [26]. These results were supported by several clinical studies found that polyphenols and foods rich in polyphenols could prevent food lipid peroxidation in the stomach absorption and accumulation of reactive carbonyls in pig and human blood systems or the modification of LDL [42][43][44][45][46][47]. We suggest that the main benefit of consuming plant polyphenols and other redox compounds in the human diet, as an integral part of the meal, arises mainly from the ability to prevent lipid peroxidation, co-oxidation of vitamins, generation of reactive aldehydes and other cytotoxic ALEs in the stomach.…”
Section: Stomachmentioning
confidence: 75%
See 1 more Smart Citation
“…Polyphenols and foods rich in polyphenols were found to inhibit food lipid peroxidation in stomach medium co-oxidation of vitamins and cholesterol and production of primary and secondary ALEs [26]. These results were supported by several clinical studies found that polyphenols and foods rich in polyphenols could prevent food lipid peroxidation in the stomach absorption and accumulation of reactive carbonyls in pig and human blood systems or the modification of LDL [42][43][44][45][46][47]. We suggest that the main benefit of consuming plant polyphenols and other redox compounds in the human diet, as an integral part of the meal, arises mainly from the ability to prevent lipid peroxidation, co-oxidation of vitamins, generation of reactive aldehydes and other cytotoxic ALEs in the stomach.…”
Section: Stomachmentioning
confidence: 75%
“…ALEsII and AGEsII in the blood system interact with RAGE (receptor of advanced glucose end products) to activate a postprandial oxidative stress [35][36][37][38][39]. Animals and humans, after ingestion of peroxidized foods, have been shown to absorb and excrete an increased amount of malondialdehyde (MDA) and other carbonyls [40][41][42]. Polyphenols and foods rich in polyphenols were found to inhibit food lipid peroxidation in stomach medium co-oxidation of vitamins and cholesterol and production of primary and secondary ALEs [26].…”
Section: Stomachmentioning
confidence: 99%
“…Moreover, cytotoxic activity, cancer-promoting effects, and the detrimental effect on the gut microbiota of DCs were reported [ 18 , 19 , 20 ]. Recently, it was highlighted that the postprandial levels of DCs depend on many variables, including physiological state, amount, and composition of food, although food intake of 3-DG was not significantly correlated with plasmatic levels of 3-DG or skin autofluorescence [ 21 ]. In terms of HMF, it can be converted in vitro and in vivo into 5-sulfoxymethylfurfural, which is known to induce genotoxic and mutagenic effect [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%